Risk Factors for Prolonged Narcotic Use Following Arthroscopic Rotator Cuff Repair. Issue 7 (21st July 2017) - Cancienne, Jourdan M.; Gwathmey, Frank Winston; Werner, Brian C.
Objectives: Narcotics are commonly prescribed for management of acute pain in the early postoperative period following arthroscopic rotator cuff repair (RCR), but little is known about the frequency and risk factors for persistent use. The goal of this study was to determine risk factors for prolonged narcotic use following arthroscopic RCR. Methods: A national insurance database was queried for patients undergoing arthroscopic RCR from 2007-2015 using CPT codes. Prolonged narcotic use was defined as a new prescription for a narcotic pain medication between 3 and 6 months following the procedure. Patients without minimum 6 months' follow-up were excluded. A multivariate logistic regression analysis was utilized to evaluate risk factors for prolonged narcotic use, including a prescription for narcotics within the 3 months before surgery, age, sex, obesity, tobacco use, alcohol use, depression and inflammatory arthritis. The regression analysis was used to control for demographics and numerous medical comorbidities. Adjusted odds ratios (OR) and 95% confidence intervals (CIs) were calculated for each risk factor, with P < 0.05 considered statistically significant. Results: 28, 331 patients met inclusion and exclusion criteria. 7, 543 patients (27%) were characterized as having prolonged narcotic use. Preoperative narcotic use was the most significant risk factor for prolonged postoperative narcotic use (OR 5.4, p < 0.0001). Age < 50 years (OR 1.4), male sex (OR 1.1), obesity (OR 1.1), morbid obesity (OR 1.4), tobacco use (OR 1.8), alcohol use (OR 1.3), inflammatory arthritis (OR 1.5) and depression (OR 2.0) were also all significant risk factors for prolonged postoperative narcotic use [Table 1]. Conclusion: More than a quarter of patients undergoing arthroscopic RCR continue to receive narcotic prescriptions more than 3 months postoperatively. The most significant risk factor for prolonged narcotic use is the use of preoperative narcotics. Additional risk factors include younger age, male sex, obesity, tobacco and alcohol use, depression and inflammatory arthritis. Table 1. Significant Risk Factors for Prolonged Narcotic Use after Arthroscopic Rotator Cuff Repair Variable Odds Ratio 95% CI P Preoperative Narcotic Use 5.43 [5.22 -5.66] < 0.0001 Age < 50 years 1.36 [1.26 - 1, 46] < 0.0001 Male Sex 1.14 [1.10 - 1.19] < 0.0001 Obesity (BMI 30-40) 1.09 [1.04 - 1.14] < 0.0001 Morbid Obesity (BMI 40+) 1.36 [1.28 - 1.45] < 0.0001 Tobacco Use 1.78 [1.70 - 1.87] < 0.0001 Alcohol Use 1.34 [1..22 - 1.46] < 0.0001 Inflammatory Arthritis 1.52 [1.42 - 1.63] < 0.0001 Depression 1.99 [1.91 - 2.08] < 0.0001